2005
DOI: 10.1128/jcm.43.9.4902-4904.2005
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough Disseminated Aspergillus ustus Infection in Allogeneic Hematopoietic Stem Cell Transplant Recipients Receiving Voriconazole or Caspofungin Prophylaxis

Abstract: Aspergillus ustus is an uncommon clinical species which is poorly susceptible to antifungals. We report two cases of A. ustus infections that occurred in allogeneic stem cell transplant recipients while they were receiving either voriconazole or caspofungin. Prolonged use of these new antifungal agents may increase the risk of the emergence of resistant organisms. CASE REPORTPatient 1 was a 29-year-old male, weighing 80 kg, who was diagnosed with acute lymphoblastic leukemia in October 2002. During initial che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
62
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 16 publications
3
62
0
Order By: Relevance
“…Antifungal susceptibility tests of A. calidoustus isolates show that most antifungal drugs have limited or no activity, which is in accordance with previous studies where "A. ustus" (A. calidoustus) isolates were found to be resistant to amphotericin B, echinocandins, and azole derivatives (5,6,21,36). The class of the triazoles has a prominent role in the management of patients with invasive aspergillosis, and breakthrough infections caused by "A. ustus" have been reported in patients treated with voriconazole and itraconazole (21).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Antifungal susceptibility tests of A. calidoustus isolates show that most antifungal drugs have limited or no activity, which is in accordance with previous studies where "A. ustus" (A. calidoustus) isolates were found to be resistant to amphotericin B, echinocandins, and azole derivatives (5,6,21,36). The class of the triazoles has a prominent role in the management of patients with invasive aspergillosis, and breakthrough infections caused by "A. ustus" have been reported in patients treated with voriconazole and itraconazole (21).…”
Section: Discussionsupporting
confidence: 78%
“…The class of the triazoles has a prominent role in the management of patients with invasive aspergillosis, and breakthrough infections caused by "A. ustus" have been reported in patients treated with voriconazole and itraconazole (21). We found that even the most recently registered compound, posaconazole, which is commonly the drug with the greatest intrinsic activity against Aspergillus species, showed no in vitro activity.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…These outbreaks of A. ustus infections may be of infection control importance, as the clinical isolates exhibited low susceptibilities to multiple antifungal drugs, as was reported previously ( 12 , 17 ). Although we do not know breakpoints of A. fumigatus resistance, results of prior studies suggest that infection with organisms requiring high MICs of amphotericin or itraconazole is associated with poor clinical outcomes ( 37 , 38 ).…”
Section: Discussionsupporting
confidence: 70%
“…Supporting this suggestion, the species was abundant in water from installations on arctic Svalbard, where water pipelines are heated because of permafrost (G. Hageskal and S. B. Rønning, unpublished results). A. ustus has not, to our knowledge, been isolated from water previously, and the finding of this fungus is particularly interesting because it has been reported from infections in humans and appears to be an emerging opportunistic pathogen in immunosuppressed patients (12,25,49). It is noteworthy that A. ustus was frequently isolated from hospital samples.…”
Section: Discussionmentioning
confidence: 96%